Badische Anilin & Soda-Fabrik dye label with pigeons (Badische Anilin- & Soda-Fabrik, 1900)
Dye label depicts pigeons standing in a lush landscape with flowers in the foreground. Decorative border includes the Badische Anilin & Soda-Fabrik (BASF) name on a banner adornment. Founded in 1865, Badische Anilin & Soda-Fabrik (BASF) was once the largest chemical factory in the world. Based in Ludwigshafen, Germany, the company first concentrated on the manufacture of synthetic dyestuffs. Key breakthroughs came in the form of the industrial production of synthetic indigo (1897) and the discovery of the indanthrene dyes (1901). Aniline dyes determined much of the firm's business. The company primarily advertised by submitting its products for awards at regional and international industrial trade fairs, especially world's fairs.
Keywords: Pigeons; Dye industry; Printed ephemera; Badische Anilin- & Soda-Fabrik; Dyes and dyeing; Birds in art; Advertising